SLEEP AS A DETERMINANT OF ACADEMIC PERFORMANCE OF UNIVERSITY STUDENTS IN OGUN STATE, SOUTH WEST, NIGERIA - Taiwo M. Williams; Ruth A. Aderanti (European Scientific Journal, ESJ, 2014)
Sleep has been found to be of the least priority of most individuals especially students. This may not be unconnected with the fact that, they feel they must always meet up with deadlines in form of school assignments and examinations. A descriptive survey design was used to find the relationship between sleep and the academic performance of University students. The population comprised undergraduate students attending Private universities in Ogun State, South-west Nigeria. Three hundred and eight participants were randomly selected for the study. The Groninger Sleep Quality Questionnaire was adapted for the purpose of this study. The scale has response choices ranging from strongly disagree to strongly agree, measuring the students’ sleep quality. The Cumulative Grade Point Average of the respondents was correlated with the amount of sleep, using Pearson moment correlation coefficient. The result shows a significant relationship between adequate / inadequate sleep and academic performance. The study has important implications for policy makers, school administrators and educators planning to improve students’ academic performance who should consider the potential benefits of taking a multidisciplinary approach at understanding and promoting the academic and behavioral wellness of the students.